Association between resting heart rate across the life course and all-cause mortality: longitudinal findings from the Medical Research Council (MRC) National Survey of Health and Development (NSHD). Issue 9 (21st May 2014) - Ó Hartaigh, Bríain; Gill, Thomas M; Shah, Imran; Hughes, Alun D; Deanfield, John E; Kuh, Diana; Hardy, Rebecca
Abstract : Background: Resting heart rate (RHR) is an independent risk factor for mortality. Nevertheless, it is unclear whether elevations in childhood and mid-adulthood RHR, including changes over time, are associated with mortality later in life. We sought to evaluate the association between RHR across the life course, along with its changes and all-cause mortality. Methods: We studied 4638 men and women from the Medical Research Council (MRC) National Survey of Health and Development (NSHD) cohort born during 1 week in 1946. RHR was obtained during childhood at ages 6, 7 and 11, and in mid-adulthood at ages 36 and 43. Using multivariable Cox regression, we calculated the HR for incident mortality according to RHR measured at each time point, along with changes in mid-adulthood RHR. Results: At age 11, those in the top fifth of the RHR distribution (≥97 bpm) had an increased adjusted hazard of 1.42 (95% CI 1.04 to 1.93) for all-cause mortality. A higher adjusted risk (HR, 95% CI 2.17, 1.40 to 3.36) of death was also observed for those in the highest fifth (≥81 bpm) at age 43. For a >25 bpm increased change in the RHR over the course of 7 years (age 36–43), the adjusted hazard was elevated more than threefold (HR, 95% CI 3.26, 1.54 to 6.90). After adjustment, RHR at ages 6, 7 and 36 were not associated with all-cause mortality. Conclusions: Elevated RHR during childhood and midlife, along with greater changes in mid-adulthood RHR, are associated with an increased risk of all-cause mortality.